Evaluación de dosis de silicio para el control de la mancha marrón (Bipolaris oryzae) en el cultivo de arroz (Oryza sativa L.) - Avellaneda Vázquez, Juan Pablo (2022)
The brown spot of rice is caused by the fungus Bipolaris oryzae and is one of the main diseases that affects all rice farmers in the world. The general objective of this research work was to evaluate different doses of silicon for the control of brown spot (Bipolaris oryzae) in rice crops (Oryza sativa L.). This research was carried out at campus "La María", Universidad Técnica Estatal de Quevedo, located at Km 7.5 Vía Quevedo - El Empalme. A completely randomized block design with 7 treatments and 3 replications was used.